Case report: Breaking CNS immuno-privilege: TNFα-inhibitor triggers aseptic meningitis in a patient with rheumatoid arthritis - Kassabian, Benedetta; Facco, Monica; Miscioscia, Alessandro; Carraro, Samuela; Rinaldi, Francesca; Gallo, Paolo; Puthenparampil, Marco (Frontiers in Immunology, 2024)
Blood-brain barrier dysfunction might be driven by peripheral inflammation. TNFα inhibitors (TNF-αi) are occasionally associated with a wide spectrum of neurological immuno-mediated disorders. However, patients with systemic autoimmune disorders, including rheumatoid arthritis (RA), might be prone to develop further organ-specific, including central nervous system (CNS), autoimmunity. Here we report the case of a patient, affected by RA and treated with etanercept, who suddenly developed focal neurological symptoms. Cerebrospinal fluid, magnetic resonance imaging (MRI), and positron emission tomography (PET)/MRI findings are reported and support the diagnosis of TNF-αi -associated aseptic meningitis.